2022
DOI: 10.1155/2022/6277139
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Molecular Mechanism of Evodia rutaecarpa Fruit in the Treatment of Nasopharyngeal Carcinoma Using Network Pharmacology and Molecular Docking

Abstract: Background. Nasopharyngeal carcinoma (NPC), a neoplasm of the head and neck, has high incidence and mortality rates in East and Southeast Asia. Evodia rutaecarpa is a tree native to Korea and China, and its fruit (hereafter referred to as Evodia) exhibits remarkable antitumour properties. However, little is known about its mechanism of action in NPC. In this study, we employed network pharmacology to identify targets of active Evodia compounds in nasopharyngeal carcinoma and generate an interaction network. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The effects of natural products on disease management may result from the combined action of various compounds 24 . First, we identified nine constituents of EFE using LC–MS/MS; rutaecarpine (Comp.1), evodiamine (Comp.2), evodol (Comp.3), dehydroevodiamine (Comp.4), limonin (Comp.5), synephrine (Comp.6), evocarpine (Comp.7), dihydroevocarpine (Comp.8), and hydroxyevodiamine (Comp.9).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of natural products on disease management may result from the combined action of various compounds 24 . First, we identified nine constituents of EFE using LC–MS/MS; rutaecarpine (Comp.1), evodiamine (Comp.2), evodol (Comp.3), dehydroevodiamine (Comp.4), limonin (Comp.5), synephrine (Comp.6), evocarpine (Comp.7), dihydroevocarpine (Comp.8), and hydroxyevodiamine (Comp.9).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%